Peran Agroforestri Kopi Arabika dalam Penyerapan Karbon di Perhutanan Sosial Desa Kekuyang, Aceh Tengah - Akhir, Jumadil; Rizaka, Farid Wajdi; Dahlan, Dahlan; Arlita, Tuti; Basri, Hairul (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2025)
Arabica coffee is one of the world's leading coffee species that grows optimally in tropical highland areas, such as Central Aceh, and is often cultivated in agroforestry systems. Coffee agroforestry not only increases agricultural productivity but also plays a vital role in carbon sequestration and environmental conservation through the presence of shade trees that store carbon in biomass. This system is globally recognized as a climate change mitigation strategy and supports ecological balance. These places are included in the 568 ha Social Forestry area, has great potential for sustainable coffee agroforestry development. This study aims to analyze the potential carbon stocks and carbon dioxide (CO₂) absorption in the Social Forestry area of Kekuyang Village, Central Aceh Regency. Data were collected using a vegetation inventory method in 28 observation plots measuring 20 m × 20 m. Tree diameter data were used to calculate biomass using allometric equations, which were then converted into carbon stocks and CO₂ absorption. The results showed a total aboveground biomass (AGB) of 55,439.20 kg, with an estimated carbon stock of 26,135.74 kg from the total area of the research plot. The potential for carbon dioxide absorption reached 85.64 tons/ha after conversion. The plant species with the largest contribution to carbon stocks was lamtoro (Leucaena leucocephala), followed by avocado (Persea americana) and Arabica coffee (Coffea arabica). The coffee agroforestry system in Kekuyang Village has proven to be ecologically effective in storing carbon and has the potential to become a model for sustainable land management that supports climate change mitigation.